Molecular genetic methods for intestinal microbiome investigation - O. L. Kardymon; A. V. Kudryavtseva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To analyse existing molecular genetic methods for investigation of specific variety and the quantitative analysis of intestinal microbiome. Summary. Intestinal microbiome disorders play the leading role in development of many diseases of infectious and noninfectious origin. Monitoring of specific type, quantitative ratio of different types and strains of microorganisms in healthy people and at various diseases is essential for to develop strategy for microbiome restitution by microbial therapy. Modern molecular genetic methods of microbial investigation combined to the established methods of classical microbiology give the chance not only to identify microorganism species and even a strain, but also to decipher their genomes, to estimate antibiotic resistance and to establish its mechanism at genetic level, to estimate specific properties of specific microbial strain that will allow to define potential and efficacy of their clinical application etc. Meanwhile, today, to distinguish species and strains of microorganisms at DNAs or RNA level, standard culture and visual method are combined to molecular biology and genetics methods even more frequently. Conclusion. In molecular biology there is a stash of methods for intestinal microbial studying that can be implied in clinical practice. However there are also promising scientific methods, yet not applicable for disease diagnostics. Results of scientific activity is gradually translated into clinical practice and become the standard for diagnosis and a basis for development of new treatment methods.